Frequency of Destructive Hip Disease Post Intra-Articular Corticosteroid Hip Injection - Fraz Noor, Aamir Waseem, Shaheryar Aziz Tarar, Naeem Mehmood Mughal, Sikandar Ali Bhurgri, Abdul Samad Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the frequency of destructive hip disease in post intra-articular corticosteroid hip Injection. Study Design: Retrospective study Place and Duration of Study: Department of Orthopaedic, Sahara Medical College Narowal from 1st January 2021 to 31st December 2021. Methodology: One hundred and twenty cases of corticosteroid injection in intra-articular region were analyzed. The radiological imaging within 6-12 months was used for finding frequency of rapidly destructive arthrosis. Narrowing of joint space greater than fifty percent with a loss of cartilage up to 2mm within a year was used for rapidly destructive arthrosis diagnosis. Kallgren and Lawrence scoring system ranged between 0-4 was used. Results: There were 73.3% and 26.7% males and mean was 53.1±3.3 years. The steroidal injection was placed as 40mg triamcinolone-acetonide with 4 mL 1% lidocaine in 77.5% of cases. 20.8% rapidly destructive arthrosis in all the patients who were injected with corticosteroid. The progression of total hip arthroplasty was noticeable in 22.5%. Conclusion: A high frequency of destructive hip disease is observed in intra-articular corticosteroid hip injections.